Combined Therapy With Swimming Exercise and a Diet Supplemented With Diphenyl Diselenide Is Effective Against Age‐Related Changes in the Hepatic Metabolism of Rats. Issue 6 (20th December 2016) - Heck, Suélen O.; Fulco, Bruna C.W.; Quines, Caroline B.; Oliveira, Carla E.S.; Leite, Marlon R.; Cechella, José L.; Nogueira, Cristina W.
ABSTRACT: Aging is characterized by a widespread loss of homeostasis in biological systems and is accompanied by pathophysiological changes including the liver injury. The aim of the present study was to investigate the effects of the combined therapy with swimming exercise (20 min session, 5 days/week during 4 weeks) and a diet supplemented with 1 ppm of (PhSe)2 on the hepatic metabolic alterations caused by aging in rats. In this study, male old Wistar rats had an increase in the epididymal fat relative weight, disturbances in the activities of hepatic enzymes associated to the glucose homeostasis, higher hepatic triglyceride content and higher activity of the plasma alanine aminotransferase (ALT), and aspartate aminotransferase (AST). The combined therapy normalized the activities of glucose‐6‐Pase and tyrosine aminotransferase, gluconeogenic enzymes, increased the hepatic glycogen content and was effective against the increase in the hepatic triglycerides content, without altering the activities of hexoquinase, and citrate synthase. Moreover, the combined therapy normalized the activities of AST and ALT, indicating a hepatoprotective effect. The combined therapy with swimming exercise and a diet supplemented with 1 ppm of (PhSe)2 contributed to the hepatic glucose homeostasis in old rats. Nevertheless, more studies are needed to investigate the possible mechanisms of action behind these effects. J. Cell. Biochem. 118: 1574–1582, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Combined therapy ameliorated age‐related hepatic metabolic alterations. Combined therapy was effective in improving hepatic glucose homeostasis in old rats combined therapy normalized the activities of AST and ALT in old rats.